EBSD Study of Uranium Alloys. Issue 44 (16th June 2016) - Drozdenko, Daria; Minarik, Peter; Paukov, Mykhaylo; Buturlim, Volodymyr; Tkach, Ilya; Havela, Ladislav
ABSTRACT: Metallographical examination of Uranium alloys can benefit from electron back scatter diffraction (EBSD) technique. Various methods of surface preparation for microstructural characterization are described and compared. The aim of the study was to optimize the preparation technique for surfaces of U alloy splats for EBSD mapping, particularly in the context of U1- x Mo x alloys, as properties of γ-U surfaces (e.g. with more Mo) are very different than for mostly α-U type (low-alloyed U).